Opinion leaders should be given a role in organisation - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 15 June 2021 - The roles played by opinion leaders have a huge impact on the development of universities that can be disseminated using verbal and non-verbal communication. Indirectly, it will stimulate the development of the university and encourage community participation within and outside the university through the role of opinion leaders.